Catalytic enantioselective Michael additions to unsaturated ester derivatives using chiral copper(II) Lewis acid complexes. - Evans, D; Willis, M; Johnston, J (1999)
[formula: see text] Chiral Cu(II) bisoxazoline (box) Lewis acids have been developed as catalysts of the Michael addition of enolsilanes to unsaturated ester derivatives. While enantioselection is stereoregular, the sense of diastereoselection is directly related to thioester enolsilane geometry: (E) enolsilanes give anti adducts and (Z) enolsilanes afford syn adducts. The size of the enolsilane alkylthio substituent directly impacts the magnitude of diastereoselection.